The effect of using chondroitin sulfate in osteoarthritis of the knee - Żaba, Ziemowit; Lisowska, Aleksandra; Żołyniak, Wojciech; Warzyszak, Paweł; Małek, Róża; Milczek, Maria; Hawranik, Izabela; Tomasik, Mikołaj; Niski, Szymon; Skrzypek, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction: Osteoarthritis is the most common disease of the musculoskeletal system. It develops in the regulation of the quality and quantity of articular cartilage, which cushions the joint and improves the sliding of the articular surfaces. Chondroitin sulfate being a natural glycosaminoglycan is found in the cartilage and extracellular matrix. The European League Against Rheumatism (EULAR) recommends the use of chondroitin sulfate in the treatment of knee osteoarthritis. Objective: The purpose of our study was to present, based on the available literature, the latest reports on the effect of chondroitin sulfate in knee osteoarthritis Methods and materials: The present study was based on available data collected in the PubMed database and published between 2001 and 2022. The study was conducted by reviewing keywords such as: , knee osteoarthritis”, , chondroitin sulfate”, , treatment” , diagnosis” State of knowledge: Joint cartilage is mainly composed of type II collagen, proteoglycans, chondrocytes and water. In healthy articular cartilage, the balance between the individual components is constantly maintained, thanks to which cartilage degradation is accompanied by its synthesis. The reviewed scientific papers evaluated the effect of chondroitin sulfate on pain in osteoarthritis. Summary: We found a large inconsistency between experimental protocols and study results. Therefore, comparing publications evaluating the actual effect of chondroitin sulfate on joint synovial tissues and biochemical markers is challenging. Additional studies are needed focusing on long-term treatment as well as evaluating their potential disease modifying effects.